Short-Term Memory Comparison Of Students Of Faculty Of Medicine Pelita Harapan University Batch 2015 Between The Handwriting And Typing Method - Widjaja, Caroline; Sumali, Stefanus Satria (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Introduction : A lot of research has been done to determine if handwriting or typing note influenced short-term memory, however, the results obtained are still controversial. Therefore this study is structured to see the effect of note taking methods by handwriting and typing on short-term memory.Aim : The aims of this study were to increase the performance of students in Faculty of Medicine Pelita Harapan University as well as providing the right and effective method of taking notes.Method : Experimental study design was chosen in this study. Study population is students of faculty of medicine Pelita Harapan University batch 2015. 40 samples will be divide randomly into two, one group will take a note by handwriting and another by typing. Each group is required to watch a video about 15 minutes long. The results were analyzed statistically using T-test.Result : The average of new information that can be remembered by group that take a note by handwriting significantly (p<0,05) higher than group than take a note by typing with a p-value of 0,009.Conclusion : Take a note by handwriting allows people to remember more new information than typing.